The effects of US monetary policy shocks: Applying external instrument identification to a dynamic factor model - Mark Kerssenfischer (Deutsche Bundesbank, 2017)
Dynamic factor models and external instrument identification are two recent advances in the empirical macroeconomic literature. This paper combines the two approaches in order to study the effects of monetary policy shocks. I use this novel framework to re-examine the effects found by Forni and Gambetti (2010, JME) in a recursively-identified DFM. Considering the fundamental differences between the identifying assumptions, the results are overall strikingly similar. Importantly, this finding stands in stark contrast to traditional VAR models, which yield decisively different results in the two identification schemes. This highlights the importance of using extended information sets to properly identify monetary policy shocks.
Keywords: C32; E32; E44; E52; F31; 330; Monetary Policy; Dynamic Factor Models; External Instrument; High-Frequency Identification